Articulações da paródia na coleção devorando Shakespeare - Nóbrega, Caio Antônio (2023)
This thesis aims at studying parody in the three novels that constitute the Devorando Shakespeare collection, published in Brazil between 2006 and 2007. The novels are Trabalhos de amor perdidos (2006), by Jorge Furtado, which parodies Shakespeare’s Love’s Labour’s Lost; A décima segunda noite (2006), by Luis Fernando Verissimo, an intertext based on the comedy Twelfth Night; Sonho de uma noite de verão (2007), by Adriana Falcão, which parodically reconstructs the events of A Midsummer Night’s Dream. In relation to these narratives, metafictional developments are analyzed in three different levels of articulation – cultural, textual-verbal and medial. Furthermore, we argue that each level is connected to a specific ethos of parody, which results in discussions about intercultural devouring, intertextual criticism – in the form of a theoretical-critical fiction – and intermedial memory. Our analysis is supported by critical and theoretical principles drawn especially from Hutcheon (2000), Rose (1979) and Dendith (2000), regarding parody; from Currie (1995), Hutcheon (1980) and Waugh (1984), in relation to metafiction; from Al-Shara (2009), Fux and Moreira (2008) and Greaney (2006), on the postulates of theoretical-critical fiction; and from Bruhn (2016), Rajewsky (2012) and Wolf (2011), in relation to intermediality. We were able to conclude that parody is a very complex creative strategy, full of nuances: the in-betweenness that nourishes parody allows for several new interpretative possibilities, several new reading keys for entering the novels, which can be very important when we consider the distortions and the new visual arrangements that result from the reflexive house of mirrors that characterizes the metafictional texts of the Devorando Shakespeare collection.